Analysis of Countercyclical Policy Effectiveness in Maintaining Bank Health in Conventional Commercial Banks Research Project - Salta; Payamta (Jurnal Multidisiplin Madani, 2023)
The Corona Virus Disease (Covid-19) outbreak has an impact on various sectors of life, not only in the health sector, all sectors are affected. The most severe and prolonged impact is the banking sector which can endanger the economic sector. Seeing these conditions, the government/Financial Services Authority (OJK) issued an economic stimulus policy (Countercyclical) to maintain bank health. The purpose of this study was to analyze the effectiveness of economic stimulus policies (Countercyclical) by comparing the health conditions of banks before Covid-19 and during Covid-19, before Covid-19 and after Covid-19, during void-19 and after Covid-19. This research is relevant to the prudential banking theory (prudential principle), banks must be managed properly or with caution because the collapse of a bank will have a systemic impact. Second, the policy theory is relevant to the actions taken by the Financial Services Authority to maintain economic and banking stability affected by the Corona Virus Disease (Covid-19). Researchers in analyzing the effectiveness of economic stimulus policies (Countercyclical) by examining the health condition of the bank with the assessment method using the RGEC method, the elements assessed are Risk Profile, Goog Corprate Governance, Earning and Capital, and other financial aspects. Researchers compared the three conditions before, during, and after coronavirus disease (Covid-19). The different test tools used were the paired sample t-test for normally distributed data and the Wilcoxon signed rank test for non-normally distributed data, SPSS version 24.0 for windows. Based on the results of data analysis shows that; There is no difference in the health of banks during Covid-19 compared to before Covid-19 for NPL Gross, NPL Net, BOPO and GCG, while ROA, LDR, CAR and NIM have differences in effective countercyclical policies. During Covid-19 conditions compared to after Covid-19 there were differences in the ratios of NPL Gross, NPL Net, BOPO, LDR, CAR and NIM while for GCG and ROA there were no differences in effective countercyclical policies. The condition of bank health before Covid-19 compared to after Covid-19 in the ratio of NPL Gross, NPL Net, BOPO, GCG had no difference in conditions while ROA.LDR, NIM and CAR had differences, meaning the policies were countercyclical effective